Price Discrimination in Public Healthcare1. (29th April 2018) - Berg, Nathan; Kim, Jeong‐Yoo
Abstract : Could a public healthcare system use price discrimination—paying medical service providers different fees, depending on the service provider's quality—lead to improvements in social welfare? We show that differentiating medical fees by quality increases social welfare relative to uniform pricing (i.e. quality‐invariant fee schedules) whenever hospitals and doctors have private information about their own ability. We also show that by moving from uniform to differentiated medical fees, the public healthcare system can effectively incentivise good doctors and hospitals (i.e. low‐cost‐types) to provide even higher levels of quality than they would under complete information. In the socially optimal quality‐differentiated medical fee system, low‐cost‐type medical‐service providers enjoy a rent due to their informational advantage. Informational rent is socially beneficial because it gives service providers a strong incentive to invest in the extra training required to deliver high‐quality services at low cost, providing yet another efficiency gain from quality‐differentiated medical fees.